Preparation method of ionic liquid dissolved nanocellulose
By dissolving cellulose using ionic liquids and then nano-sizing it in an ethanol-water antisolvent, the problems of high energy consumption and low yield in existing technologies have been solved. This method enables the efficient and low-cost preparation of nanocellulose, which is applicable to a variety of natural raw materials and has broad application prospects.
Patent Information
- Application Number
- CN202511424343.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2026-01-09
AI Technical Summary
Existing methods for preparing nanocellulose are energy-intensive, require large amounts of chemical reagents, and have low yields, which limits their large-scale production and widespread application.
The ionic liquid dissolution method involves mixing cellulose raw materials with ionic liquid, heating and stirring to dissolve them, then nano-processing them in an ethanol-water antisolvent, and finally separating the nanocellulose by washing with water and recovering the ionic liquid. This method is applicable to a variety of natural raw materials.
It significantly improves cellulose dissolution efficiency and product yield, with yields reaching 80-95%. The prepared nanocellulose has a degree of polymerization of 120-3000, a zeta potential as high as -40mV, and a dispersion viscosity of 10-300Pa·s. The process is green and environmentally friendly, the ionic liquid can be recycled, and costs are reduced.
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of nanocellulose materials, and specifically discloses a method for preparing high-yield soluble nanocellulose based on ionic liquid dissolution process. Background Technology
[0002] Cellulose is one of the most abundant renewable natural polymers on Earth. Its derivative, nanocellulose, has high specific surface area, high strength, good mechanical, thermal, rheological properties, and biocompatibility, and shows broad application potential in packaging, composite materials, medical carriers, electronic devices, and other fields.
[0003] Currently, the main methods for preparing nanocellulose include mechanical, chemical, and enzymatic methods. While mechanical methods are simple to operate, they are energy-intensive and have low yields; chemical methods require the use of strong acids or strong oxidants, posing risks of environmental pollution and damage to the cellulose structure; enzymatic methods are mild, but have long reaction cycles, high overall costs, and limited applicability.
[0004] The aforementioned problems have significantly limited the application and promotion of nanocellulose, indirectly increasing economic and technological barriers and hindering its large-scale production and widespread application.
[0005] Therefore, it is necessary to provide a method for preparing nanocellulose that is efficient, green, low-cost, high-yield, and has great potential for large-scale production. Summary of the Invention
[0006] To overcome the shortcomings and deficiencies of existing technologies, the present invention aims to provide a method for preparing ionic liquid-dissolved nanocellulose. This method can significantly improve the cellulose dissolution efficiency and product yield, achieving a yield of 80%–95%. The resulting nanocellulose has a degree of polymerization of 120–3000, a zeta potential as high as -40 mV, and a dispersion viscosity of 10–300 Pa·s. This method avoids the problems of high energy consumption, high chemical reagent consumption, and low yield associated with traditional methods. The ionic liquid used is recyclable (recovery rate ≥99%), and it is applicable to various natural raw materials such as microcrystalline cellulose, bleached bamboo pulp, and cotton, showing broad application prospects.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] A method for preparing ionic liquid-soluble nanocellulose includes the following steps:
[0009] 1) Mix cellulose raw material with ionic liquid, heat and stir to dissolve, and obtain cellulose solution;
[0010] The ionic liquid is 1-propyl-3-methylimidazolium chloride (bromine), 1-butyl-3-methylimidazolium chloride (bromine), 1-ethyl-3-methylimidazolium chloride (bromine), 1,5-diazabicyclo[4.3.0]-5-nonen-alkane chloride (C5~C60). 10 ), 1,8-diazabicycloundec-7-ene-alkane chloride (C5~C 10 One or more of the following;
[0011] 2) The cellulose solution was added to an ethanol-water antisolvent for nano-sizing treatment, washed with water to separate the nanocellulose, and the ionic liquid was recovered.
[0012] 1,5-Diazabicyclo[4.3.0]-5-nonene-alkane chloride, wherein the alkane chloride is C5~C6. 10 Alkyl chlorides, specifically 1,5-diazabicyclo[4.3.0]-5-nonene and C5-C64 chlorides. 10 Alkyl chloride (RCl, R is C5-C6) 10 It is obtained by reaction of alkane group; C5~C 10 The alkane chlorides are 1-chloropentane, 1-chlorohexane, 1-chloro-heptane, 1-chlorooctane, 1-chlorononane, and 1-chlorodecane; 1,5-diazabicyclo[4.3.0]-5-nonene and C5~C 10 The molar ratio of alkane chlorides is 1:1.
[0013] 1,8-diazabicycloundec-7-ene-alkane chlorides, wherein the alkane chlorides are C5 to C6. 10 Alkyl chlorides, specifically alkane chlorides, are formed by the reaction of 1,8-diazabicycloundec-7-ene with C5-C64 chlorides. 10 Alkyl chloride (RCl, R is C5-C6) 10 It is obtained by reaction of alkane group; C5~C 10 The alkane chlorides are 1-chloropentane, 1-chlorohexane, 1-chloro-heptane, 1-chlorooctane, 1-chlorononane, and 1-chlorodecane; 1,8-diazabicycloundec-7-ene and C5-C6 chlorides. 10 The molar ratio of alkane chlorides is 1:1.
[0014] The cellulose raw materials include one or more of the following: microcrystalline cellulose, rice straw pulp, hemp, coconut shell fiber, pomegranate peel, bamboo pulp, cotton, kapok, cotton linters, sulfate bleached wood pulp, and reed pulp; if necessary, they shall be crushed and sieved to achieve a particle size ≤500μm.
[0015] The heating and melting temperature is 80–110°C. The stirring speed is 100–800 rpm.
[0016] The cellulose raw material is 1–10 wt% of the ionic liquid.
[0017] In step 1), the ionic liquid is heated and then mixed with the cellulose raw material and stirred to obtain a cellulose solution.
[0018] In step 2), the mass ratio of the cellulose solution to the ethanol-water antisolvent is 1:(1-10).
[0019] The mass ratio of water to ethanol in the antisolvent of ethanol-water is (60-90):(10-40).
[0020] The nano-sizing process includes one or more of the following: high-speed shearing (≥10,000 rpm, 5-20 min), ultrasonic treatment (≥400 W, 5-30 min), homogenization (≥8,000 rpm, 5-25 min), and grinding and loosening (≥30 bar, 2-20 min).
[0021] The high-speed shearing rate is 10,000–30,000 rpm; the ultrasonic power is 400–800 W; the homogenization speed is 8,000–20,000 rpm; and the grinding and disintegration pressure is 30–100 bar.
[0022] The washing methods include one or more of centrifugation (≥3,000 rpm, 5-20 min), filtration (50-500 mesh), pressing (3-50 MPa), and dialysis (500-4000 kDa).
[0023] The centrifuge speed is 3000-8000 rpm.
[0024] After washing, the nanocellulose is separated; then the washing liquid is filtered, the water is evaporated, and the ionic liquid is recovered.
[0025] The method for preparing ionic liquid-soluble nanocellulose in this invention utilizes dissolution instead of mechanical and chemical processing, avoiding environmental pollution and making the process green and environmentally friendly.
[0026] This invention is compatible with a variety of cellulose raw materials and a variety of ionic liquid cellulose solvents. The process is simple and the conditions are mild, with good raw material flexibility and applicability.
[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0028] This invention achieves the preparation of ionic liquid-dissolved nanocellulose with a product yield as high as 80-95%. This invention is applicable to various natural cellulose raw materials, such as bamboo pulp, wood pulp, and cotton, and has wide process applicability. The method of this invention is simple, energy-saving, and low-consumption, offering certain production advantages. The selected ionic liquid cellulose solvent can be recycled with a high recovery rate, effectively reducing costs and environmental burden. Detailed Implementation
[0029] The present invention will be described in further detail below with reference to specific embodiments, but the implementation of the present invention is not limited thereto.
[0030] Example 1:
[0031] The preparation method of the ionic liquid-soluble nanocellulose includes the following steps:
[0032] 1) 1,5-diazabicyclo[4.3.0]-5-nonene-alkane chloride (C5) (1,5-diazabicyclo[4.3.0]-5-nonene and 1-chloropentane were reacted at 60℃ and stirred at 300rpm for 24h in a 1:1 molar ratio) Heated to 90℃, 3% by mass of kapok was added as ionic liquid, and stirred at 300rpm for 2h to mix and dissolve to obtain cellulose solution;
[0033] 2) Mix water and ethanol in a 50:50 mass ratio and heat to 90°C to obtain an antisolvent;
[0034] 3) With a cellulose solution and antisolvent in a 1:1 mass ratio, the antisolvent was slowly added to the cellulose solution for homogenization (15,000 rpm, 10 min) and ultrasonic treatment (450 W, 5 min) to obtain a nanocellulose dispersion.
[0035] 4) The nanocellulose dispersion was washed with water by pressing (10 MPa) to obtain nanocellulose with a yield of 92%, a degree of polymerization of 1300, a zeta potential of -23 mV, and a viscosity of 150 Pa·s.
[0036] 5) After filtering the filtrate, water was removed by rotary evaporation to recover the ionic liquid, with a recovery rate of 99.3%.
[0037] Example 2:
[0038] A method for preparing ionic liquid-soluble nanocellulose includes the following steps:
[0039] 1) 1-propyl-3-methylimidazolium bromide (1-propyl-3-methylimidazolium bromide) was heated to 100°C, and 5% by weight of coconut shell fiber was added to the ionic liquid. The mixture was stirred at 150 rpm for 2 hours to mix and dissolve, and then a cellulose solution was obtained.
[0040] 2) Dissolve water and ethanol in a 70:30 mass ratio and heat to 100°C to obtain an antisolvent;
[0041] 3) With a mass ratio of cellulose solution to antisolvent of 1:2, the antisolvent was slowly added to the cellulose solution and subjected to high-speed shearing (12,000 rpm, 5 min) and ultrasonic treatment (450 W, 12 min) to obtain a nanocellulose dispersion.
[0042] 4) The nanocellulose dispersion was washed by dialysis (1000 kDa) to obtain nanocellulose with a yield of 83%, a degree of polymerization of 780, a Zeta potential of -32 mV, and a viscosity of 50 Pa·s.
[0043] 5) After filtering the filtrate, the ionic liquid is recovered by rotary evaporation to remove water, with a recovery rate of 99.5%.
[0044] Example 3:
[0045] The preparation method of the ionic liquid-soluble nanocellulose includes the following steps:
[0046] 1) 1-Butyl-3-methylimidazolium chloride was heated to 110°C, and microcrystalline cellulose was added to the solvent at a mass ratio of 1%. The mixture was stirred at 400 rpm for 2 hours to mix and dissolve, and then a cellulose solution was obtained.
[0047] 2) Dissolve water and ethanol in a 60:40 mass ratio and heat to 100°C to obtain the antisolvent;
[0048] 3) With a mass ratio of cellulose solution to antisolvent of 1:4, the antisolvent was slowly added to the cellulose solution and the mixture was ground and disintegrated (30 bar, 20 min) to obtain a nanocellulose dispersion.
[0049] 4) The nanocellulose was washed by centrifugation (6,000 rpm, 20 min) to obtain nanocellulose with a yield of 81%, a degree of polymerization of 170, a Zeta potential of -39 mV, and a viscosity of 20 Pa·s.
[0050] 5) After filtering the filtrate, the ionic liquid is recovered by rotary evaporation to remove water, with a recovery rate of 99.1%.
[0051] Example 4:
[0052] The preparation method of the ionic liquid-soluble nanocellulose includes the following steps:
[0053] 1) 1,8-diazabicycloundec-7-ene-alkane chloride (C 10 (1,8-diazabicycloundec-7-ene and 1-chlorodecane were reacted at a molar ratio of 1:1 at 65°C and stirred at 300 rpm to obtain) The solution was heated to 90°C, and cotton was added to the solvent at a mass ratio of 2%. The solution was stirred at 150 rpm for 2 hours to mix and dissolve, thus obtaining a cellulose solution.
[0054] 2) Dissolve water and ethanol in a 90:10 mass ratio and heat to 90°C to obtain an antisolvent;
[0055] 3) With a mass ratio of cellulose solution to antisolvent of 1:8, the antisolvent was slowly added to the cellulose solution and the mixture was ground and disintegrated (50 bar, 10 min) to obtain a nanocellulose dispersion.
[0056] 4) The nanocellulose was washed by filtration (200 mesh) to obtain nanocellulose with a yield of 94%, a degree of polymerization of 2460, a Zeta potential of -20mV, and a viscosity of 280Pa·s.
[0057] 5) After filtering the filtrate, the ionic liquid is recovered by rotary evaporation to remove water, with a recovery rate of 99.4%.
[0058] Example 5:
[0059] A method for preparing ionic liquid-soluble nanocellulose includes the following steps:
[0060] 1) Mix ionic liquids 1,5-diazabicyclo[4.3.0]-5-nonene-alkane chloride (C5) and 1,5-diazabicyclo[4.3.0]-5-nonene-alkane chloride (C10) in a 1:1 mass ratio (1,5-diazabicyclo[4.3.0]-5-nonene and 1-chlorodecane were reacted at 60℃ and 300rpm in a 1:1 molar ratio). Heat to 90℃, add 4% (by mass) of cotton wool of the ionic liquid, and stir at 200rpm for 1h to mix and dissolve to obtain a cellulose solution.
[0061] 2) Dissolve water and ethanol in a mass ratio of 80:20 and heat to 90°C to obtain an antisolvent;
[0062] 3) With a mass ratio of cellulose solution to antisolvent of 1:4, the antisolvent was slowly added to the cellulose solution and the mixture was ground and disintegrated (30 bar, 20 min) to obtain a nanocellulose dispersion.
[0063] 4) The nanocellulose was washed by filtration (200 mesh) to obtain nanocellulose with a yield of 89%, a degree of polymerization of 1986, a Zeta potential of -23mV, and a viscosity of 240Pa·s.
[0064] 5) After filtering the filtrate, water is removed by rotary evaporation to recover the ionic liquid, with a recovery rate of 99.3%.
[0065] Example 6:
[0066] The preparation method of the ionic liquid-soluble nanocellulose includes the following steps:
[0067] 1) Mix ionic liquids 1,5-diazabicyclo[4.3.0]-5-nonene-alkane chloride (C5) and 1,8-diazabicycloundec-7-ene-alkane chloride (C5) at a mass ratio of 2:1. 10 Heat the mixture to 90°C, add 5% (by weight) of wood pulp containing ionic liquid, and stir at 300 rpm for 1 hour to mix and dissolve to obtain a cellulose solution.
[0068] 2) Dissolve water and ethanol in a mass ratio of 75:35 and heat to 90°C to obtain an antisolvent;
[0069] 3) With a mass ratio of cellulose solution to antisolvent of 1:4, the antisolvent was slowly added to the cellulose solution and subjected to high-speed shearing (15,000 rpm, 20 min) to obtain a nanocellulose dispersion.
[0070] 4) The nanocellulose was washed by centrifugation (8,000 rpm, 10 min) to obtain nanocellulose with a yield of 85.3%, a degree of polymerization of 631, a Zeta potential of -34 mV, and a viscosity of 74 Pa·s.
[0071] 5) After filtering the filtrate, the ionic liquid is recovered by rotary evaporation to remove water, with a recovery rate of 99.7%.
Claims
1. A method for preparing ionic liquid-soluble nanocellulose, characterized in that: Includes the following steps: 1) Mix cellulose raw material with ionic liquid, heat and stir to dissolve, and obtain cellulose solution; The ionic liquid is one or more of the following: 1-propyl-3-methylimidazolium bromide, 1-propyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium chloride, 1,5-diazabicyclo[4.3.0]-5-nonen-alkane chloride, and 1,8-diazabicycloundec-7-ene-alkane chloride; wherein the alkane chloride in the 1,5-diazabicyclo[4.3.0]-5-nonen-alkane chloride is C5 to C6. 10 Alkane chlorides; 1,8-diazabicycloundec-7-ene-alkane chlorides, wherein the alkane chlorides are C5 to C6. 10 Alkyl chlorides; 2) The cellulose solution was added to an ethanol-water antisolvent for nano-sizing, washed with water to separate the nanocellulose, and the ionic liquid was recovered; In step 2), the mass ratio of water to ethanol in the ethanol-water antisolvent is (60-90):(10-40); The nano-sizing process includes one or more of the following: high-speed shearing, ultrasonic treatment, homogenization, and grinding / removal. The high-speed shearing speed is ≥10,000 rpm, and the high-speed shearing time is 5-20 min; the ultrasonic treatment power is ≥400W, and the ultrasonic treatment time is 5-30 min; the homogenization speed is ≥8,000 rpm, and the homogenization time is 5-25 min; the grinding and loosening conditions are: pressure ≥30 bar, and time is 2-20 min.
2. The method for preparing ionic liquid-soluble nanocellulose according to claim 1, characterized in that: The 1,5-diazabicyclo[4.3.0]-5-nonene-alkane chloride is formed by reacting 1,5-diazabicyclo[4.3.0]-5-nonene with C5-C64 compounds. 10 Obtained by alkane chloride reaction; C5~C 10 The alkane chlorides are 1-chloropentane, 1-chlorohexane, 1-chloro-heptane, 1-chlorooctane, 1-chlorononane, and 1-chlorodecane; 1,5-diazabicyclo[4.3.0]-5-nonene and C5~C 10 The molar ratio of alkane chlorides is 1:1; 1,8-diazabicycloundec-7-ene-alkane chloride is formed by reacting 1,8-diazabicycloundec-7-ene with C5-C64 chloride. 10 Obtained by alkane chloride reaction; C5~C 10 The alkane chlorides are 1-chloropentane, 1-chlorohexane, 1-chloro-heptane, 1-chlorooctane, 1-chlorononane, and 1-chlorodecane; 1,8-diazabicycloundec-7-ene and C5-C6 chlorides. 10 The molar ratio of alkane chlorides is 1:
1.
3. The method for preparing ionic liquid-soluble nanocellulose according to claim 1, characterized in that: The cellulose raw materials include one or more of the following: microcrystalline cellulose, rice straw pulp, hemp, coconut fiber, pomegranate peel, bamboo pulp, cotton, kapok, cotton linters, sulfate bleached wood pulp, and reed pulp. The cellulose raw material is 1 to 10 wt% of the ionic liquid.
4. The method for preparing ionic liquid-soluble nanocellulose according to claim 1, characterized in that: The heating and dissolving temperature in step 1) is 80–110°C; the stirring speed is 100–800 rpm. In step 2), the mass ratio of the cellulose solution to the ethanol-water antisolvent is 1:(1-10).
5. The method for preparing ionic liquid-soluble nanocellulose according to claim 1, characterized in that: In step 2), the shearing rate of high-speed shearing is 10,000 to 30,000 rpm; the power of ultrasonic waves is 400 to 800 W; the rotation speed of homogenization is 8,000 to 20,000 rpm; and the pressure of grinding and disintegration is 30 to 100 bar.
6. The method for preparing ionic liquid-soluble nanocellulose according to claim 1, characterized in that: The washing methods described in step 2) include one or more of centrifugation, filtration, pressing, and dialysis; Centrifugation conditions: speed ≥ 3,000 rpm, 5-20 min; filtration mesh size 50-500 mesh; pressing pressure 3-50 MPa; dialysis conditions 500-4000 kDa dialysis membrane.
7. The method for preparing ionic liquid-soluble nanocellulose according to claim 1, characterized in that: In step 1), the ionic liquid is heated and then mixed with the cellulose raw material and stirred to obtain a cellulose solution; After washing in step 2), nanocellulose is separated; then the washing liquid is filtered, water is evaporated, and ionic liquid is recovered.
8. An ionic liquid-soluble nanocellulose obtained by the preparation method according to any one of claims 1 to 7.
